Adherence of stroke patients with an online brain training program: the role of health professionals' support. Issue 5 (4th July 2018) - Wentink, M. M.; Meesters, J.; Berger, M. A. M.; de Kloet, A. J.; Stevens, E.; Band, G. P. H.; Kromme, C. H.; Wolterbeek, R.; Goossens, P. H.; Vliet Vlieland, T. P. M.
Abstract: Background Computer-based cognitive rehabilitation is used to improve cognitive functioning after stroke. However, knowledge on adherence rates of stroke patients is limited. Objective To describe stroke patients' adherence with a brain training program using two frequencies of health professionals' supervision. Methods This study is part of a randomized controlled trial comparing the effect of the brain training program (600 min playtime with weekly supervision) with a passive intervention in patients with self-perceived cognitive impairments after stroke. Patients randomized to the control condition were offered the brain training after the trial and received supervision twice (vs weekly in intervention group). Adherence was determined using data from the study website. Logistic regression analyses were used to examine the impact of supervision on adherence. Results 53 patients allocated to the intervention group (group S8; 64% male, mean age 59) and 52 patients who were offered the intervention after the trial (group S2; 59% male, mean age 59) started the brain training. The median playtime was 562 min (range 63–1264) in group S8 vs. 193 min (range 27–2162) in group S2 ( p < 0.001, Mann Whitney U). Conclusions The overall adherence of stroke patients with a brain training was low and there are some implications that systematic, regular interaction with a supervisor can increase training adherence of stroke patients with a restitution-focused intervention performed at home.